The Use of Songs as Teaching Media to Improve Students’ Pronunciation Fluency - Sanerita Tresnawaty Olii (AIBPM Publisher, 2021)
The use of songs to improve student’s fluency is not only for pleasant study but also for enriching their vocabulary. This research paper is to investigate song effectivity as teaching media to improve university students’ fluency. To answer the research question, this study used the pertinence of classroom observations, by using songs and documents. The result results indicate that songs are effective to improve students’ pronunciation.